Measuring Students Speaking Anxiety in English Academic Speaking Class and Strategies to Overcome - Diovano Ardin Rachmanta (Indonesian Journal Publisher, 2026)
This study aims to measure students’ speaking anxiety levels in an English academic speaking class, identify the causes of their anxiety, and examine the strategies they use to overcome it. This study employed a mixed-methods approach by combining quantitative and qualitative data. The quantitative data were collected through a Foreign Language Classroom Anxiety Scale (FLCAS) questionnaire to measure students’ anxiety levels, while qualitative data were obtained from semi-structured interviews to explore the causes and coping strategies. The participants were university students enrolled in an academic speaking class. The findings show that 36.8% of students experience high speaking anxiety, while 63.2% fall into moderate to low levels, including 21.1% categorized as low anxiety. The study identifies three main factors causing anxiety: communication apprehension, test anxiety, and fear of negative evaluation. Students experience symptoms such as nervousness, trembling, heart pounding, lack of confidence, and fear of making mistakes or being negatively judged. To overcome anxiety, students commonly apply strategies such as preparation, relaxation (e.g., deep breathing), and positive thinking. The findings suggest that educators should implement targeted interventions by creating supportive classroom environments and integrating anxiety-reduction strategies into teaching practices. These efforts are important to enhance students’ confidence, participation, and performance in academic speaking contexts.